Assessing the Adoption of High Iron Bean Varieties and Their Impact on Iron Intakes and Other Livelihood Outcomes in Rwanda: Listing Exercise Report - Asare-Marfo, Dorene; Herrington, Caitlin; Alwang, Jeffrey; Birachi, Eliud; Birol, Ekin; Diressie, Michael Tedla; Dusenge, Leonidas; Funes, José; Katungi, Enid; Labarta, Ricardo; LaRochelle, Catherine; Katsvairo, Lister; et al. (International Food Policy Research Institute, 2016)
An impact assessment (IA) study was conducted in Rwanda in 2015 Season B in order to establish the adoption rates of HIB varieties among rural bean producing and to generate useful information on delivery and breeding efforts by analyzing the facilitating/hindering factors to adoption and diffusion of HIB varieties. A nationally representative listing exercise preceded the main household survey for the impact assessment. The listing exercise was conducted across 120 rural villages in 29 provinces of Rwanda and was administered to a total of 19,575 households. The aims of the listing exercise were to determine the adoption rate of High Iron Beans (HIBs) and to inform second-stage sampling for the main impact assessment survey that was to follow. This report presents results from the listing exercise.